2016
DOI: 10.15446/rcp.v25n1.46921
|View full text |Cite
|
Sign up to set email alerts
|

Factores que Influyen en el Desarrollo y Rendimiento Escolar de los Jóvenes de Bachillerato

Abstract: <p>El objetivo de este estudio fue analizar las variables que influyen en el aprovechamiento escolar de los jóvenes. Se configuró una batería de pruebas para medir autoeficacia, autodeterminación, autorregulación, aspectos del contexto escolar y familiar, y espiritualidad. La muestra fue de 250 estudiantes regulares de nivel medio superior. Se estimaron estadísticas univariadas, se calcularon índices y se probó un modelo de ecuaciones estructurales en el que se formaron 2 factores: desarrollo positivo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 15 publications
0
6
0
13
Order By: Relevance
“…Especialmente no que diz respeito a aprendizagem, a presença de problemas emocionais e de comportamento podem prejudicar o rendimento escolar (Gaxiola & Frías, 2016). Estudos brasileiros indicam que o baixo rendimento escolar associado aos problemas emocionais e de comportamento está entre as principais queixas que motivam a busca pelos serviços de saúde mental (Gauy, 2016;Santos, 2006;Valverde, Vitalle, Sampaio, & Schoen, 2012).…”
unclassified
“…Especialmente no que diz respeito a aprendizagem, a presença de problemas emocionais e de comportamento podem prejudicar o rendimento escolar (Gaxiola & Frías, 2016). Estudos brasileiros indicam que o baixo rendimento escolar associado aos problemas emocionais e de comportamento está entre as principais queixas que motivam a busca pelos serviços de saúde mental (Gauy, 2016;Santos, 2006;Valverde, Vitalle, Sampaio, & Schoen, 2012).…”
unclassified
“…Likewise, other important finding from this research was that the students from the first semester scored higher, that the rest of the students, in the learning strategies and school wellbeing. One possible explanation to this result rest in the proposal of other authors who mentioned that the motivational aspects related with the goals that the students establish in their learning process, which allow them to guide their interest in specific information and to gather the strategies needed to appropriate it in their knowledge baggage [23]. Considering this, we could say that the students from the first semester have higher expectations related to the learning they expect to gather, which might diminish as the students move forward to higher semesters, showing an increase at the last semester, maybe because it includes activities in real work situations, which results interesting for them.…”
Section: /11mentioning
confidence: 99%
“…However, when analyzing the results of the studies, regardless of the instrument used, an approximation between the social domains investigated and the themes pertinent to the reality of each domain (school, family, peer group and community) could be observed. In studies emphasizing academic skills, one of the PYD resources focused on the school context, it was found that self-effi cacy was signifi cantly associated with academic performance in general, and with areas, such as arts, sciences, languages, social and mathematics (Contreras et al, 2005;Gaxiola & Armenta, 2016). There were also signifi cant differences in the beliefs of the students regarding academic self-effi cacy (in the dimensions involving self-effi cacy to learn and act in school life) according to the educational level of the parents (Guerreiro-Casanova et al, 2011).…”
Section: Implications Of the Association Between Self-effi Cacy And Pmentioning
confidence: 99%